2022
DOI: 10.9734/aprj/2022/v10i3191
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic Acid Enhances the Germination and Growth of Maize under Salinity Stress

Abstract: Soil salinity is the major limiting factor restricting plant growth and development. Little is known about the comparative and combined effects of gibberellic acid (GA3) seed priming and foliar application on maize under salt stress. The current study determined the impact of different concentrations of GA3 on morpho-physiological and photosynthetic attributes of maize seedlings under salinity stress treatments (no salinity and severe salinity-15 dSm-1). The GA3 treatments consisted of 1mM, 2mM, 3mM, 4mM and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…These outcomes are consistent with past studies [47], which shown that applying GA3 increased the chlorophyll content of leaves. When maize was exposed to salt stress, foliar SA treatment significantly improved the amount of chlorophyll in the plant [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These outcomes are consistent with past studies [47], which shown that applying GA3 increased the chlorophyll content of leaves. When maize was exposed to salt stress, foliar SA treatment significantly improved the amount of chlorophyll in the plant [20].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining a sufficient water level is an essential physiological step for keeping normal development progression in plants under salt stress [20]. RWC is a well-known indicator of water status in plants since it is a water-related feature [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of IAA and CTK increased grain yield, 1000-grain weight and filled-grain percentage of rice under salt stress ( Javid et al., 2011 ). The application of GA 3 improved maize growth under salt stress ( Rauf et al., 2022 ). It was well established and known that 6-BA could promote plant cell division, inhibit and scavenge free radicals, delay leaf senescence, increase DM and N accumulation ( Roitsch and Ehneß, 2000 ).…”
Section: Introductionmentioning
confidence: 99%